Prediction of male basketball players` adult stature from the age of 13 years using chronological age and maturity - Pineau, J. C. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The purpose of this study was to cross-validate and demonstrate how adult stature can be predicted in 13-year-old basket-ball players by using a new reference specific growth curve obtained from chronological age, and maturity of sedentary boys. METHODS: The prediction of adult stature of young male basketball players was established from the results of a longitudinal study in which we developed from 125 sedentary boys aged from 12 to 17.5 years new growth curves using chronological and biological maturation. In partnership with the French basketball federation, we collected information on stature, age and secondary pubertal stages from a sample of 106 boys aged from 160 and 164 months. The participants were regional level basketball players whose adult statures were known. The association of biological maturation at a chronological age was the determining criterion to predict individual adult stature with advanced, standard and delayed puberty. RESULTS: The average longitudinal growth curves enabled the prediction of adult stature within ±3 cm, 98% of the time in male basketball players. The relationship between estimated adult stature and final stature was high (r=0.98) with a low standard error estimate (SEE=1.65 cm). Mean and standard deviation of the differences between estimated stature and adult stature were 0.7±1.7. CONCLUSIONS: This technique is a valid, nonintrusive and accurate method of predicting adult stature in adolescent basketball players. It constitutes an advance in the detection and the orientation of future basketball players.